A scoping review of lablab production in Tanzania: global perspectives on roles, challenges, and opportunities - Ndibalema, Leonard R.; Alavaisha, Edmond; Masama, Edmore; Manoko, Mkabwa L. K.; Joseph, Charles O. (Frontiers in Agronomy, 2026)
Lablab (Lablab purpureus) is a resilient, multipurpose legume with potential to improve food and feed security, enhance soil fertility, and support climate-resilient agriculture in Tanzania’s dryland regions; however, comprehensive syntheses of its agronomic, socioeconomic, and ecological roles remain limited. To address this, a scoping review was conducted of studies published between January 2000 and June 2025 in Tanzania and comparable dryland agroecological zones in Sub-Saharan Africa. Systematic searches in Scopus and Google Scholar used structured Boolean strings including keywords related to lablab, dryland farming, forage, fodder, intercropping, nitrogen fixation, soil fertility, pests, diseases, market access, and adoption potential, and reference lists of included studies were screened manually. Of 120 full-text articles assessed, 85 met inclusion criteria and were analyzed thematically. Results show that lablab is well-adapted to semi-arid and dryland zones, contributes to soil health, supports livestock feed and human nutrition, and enhances climate-resilient farming systems, while adoption is constrained by limited farmer awareness, inadequate agronomic knowledge, scarcity of improved seeds, weak market linkages, and climate variability. These findings provide a structured evidence map of lablab’s roles, challenges, and potential, highlighting opportunities for coordinated interventions targeting seed systems, value chains, and extension services to facilitate mainstreaming, promote resilient low-input agricultural systems, and support sustainable livelihoods.